Knowledge Regarding Weight Management through Lifestyle Modification among Overweight and Obese Type 2 Diabetes Mellitus Patients - Powsiga, U.; Coonghe, P.A.D.; Aravinthan, M.; Kamalarupan, L. (General Sir John Kotelawala Defence University, 2020)
Energy intake in excess of the requirement and physical inactivity are resulting in over weight and obesity, which are the major driving forces behind escalating type-2 diabetes epidemics worldwide. This study aimed to assess the knowledge regarding weight management through lifestyle modification and assess the relationship between socio demographic factors associated with knowledge among overweight and obese type 2 diabetic patients attending the Diabetic clinic at the Teaching Hospital, Jaffna. The study was a hospital based descriptive cross-sectional study that was carried out among 414 patients. Data were collected using an interviewer administered questionnaire. Data were analyzed using SPSS version 22. Chi-squire test was used to determine the factors affecting the knowledge. Study participants' age range was from 27-81years and the mean age was 56.1. Among the study participants, 28.3% were overweight and 71.7% were obese. Most of them were females (74.6%). Only 2.4% of the participants knew the healthy BMI range for Sri Lankans. Only 13.8% of the participants knew whether they were obese or overweight. Most of the participants knew that excess calorie intake (77.8%), physical inactivity (99.8%), and family history (88.4%) were the causes of overweight and obesity. The majority of the participants stated that following a proper diet (100%) and doing regular exercises were healthy ways to maintain ideal body weight. Nearly 25.6%, 18.4% of the participants correctly said the minimal duration to perform an exercise in a day for overweight, obese person respectively. Most of the participants (81.2%) had good knowledge of weight management through lifestyle modifications. However further studies should be done to assess their practice pattern.
Keywords: Weight management; Life style modification; Overweight; Obesity